Ekoteologi Perkotaan Dan Kebijakan Usaha Kepariwisataan: Analisis Filsafat Politik Atas Polemik Diskotik, Pub, Dan Karaoke Di Kota Serang - Muchtar Solihin; Nana Supiana; Munir (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2025)
This study dissects the complexity of the polemic surrounding nightlife entertainment businesses (discotheques, pubs, and karaoke) in Serang City by juxtaposing the theoretical frameworks of Urban Ecotheology and Political Philosophy analysis. Serang City, characterized as a religious city and a government center, faces a dilemma between the imperative of economic development in the tourism sector and the pressure to maintain a socio-cultural-ecological order imbued with religiosity. A qualitative research method with a critical-philosophical approach was applied through policy studies, media discourse analysis, and in-depth interviews with multi-stakeholders. The findings reveal that this polemic is not merely a simple moral conflict but a manifestation of a larger discursive struggle between the ideological concept of “halal tourism” and conventional capitalist tourism. Political philosophy analysis identifies the role of local government as both an arena and an actor experiencing internal contradictions: on one hand, it seeks to regulate in the name of public order and morality, while on the other, it is compelled to accommodate capital interests and tax revenue. From the perspective of urban ecotheology, this conflict indicates a spiritual-ecological disorientation in urban spatial governance, where space is reduced to mere economic commodity, detached from the context of community sacrality and sustainability. This study concludes that sustainable solutions require the reconstruction of tourism policies based on an “ecotheological urban planning philosophy,” a paradigm that integrates spatial justice, environmental sustainability, and local cultural resilience within a deliberative and inclusive policy framework.